2018
DOI: 10.1111/adj.12624
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of stabilized hydroxyapatite nanosuspensions for enamel caries remineralization

Abstract: High-pressure homogenization is an effective method for facile preparation of a stable suspension of hydroxyapatite nanoparticles. Treatment of artificial lesions with nonagglomerated spherical HA nanoparticles improves the remineralization of enamel lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In remineralization studies in which HA was used alone, it was found to have positive results on the enamel. 21 Also, studies of children who chew Xylitol gum have found it successful in preventing caries. 22 Our results suggest that the co-use of HA, fluoride, and xylitol use may be beneficial in initial enamel lesions, although further studies of this issue are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In remineralization studies in which HA was used alone, it was found to have positive results on the enamel. 21 Also, studies of children who chew Xylitol gum have found it successful in preventing caries. 22 Our results suggest that the co-use of HA, fluoride, and xylitol use may be beneficial in initial enamel lesions, although further studies of this issue are needed.…”
Section: Discussionmentioning
confidence: 99%
“…To create initial enamel lesions, a demineralisation solution (pH 4.5) was prepared by the Atatürk University Faculty of Pharmacy. The demineralisation solution was prepared as 0.075 mol/L acetic acid, 0.002 mol/L Ca (from CaCl 2 ) and 0.002 mol/L P (from potassium phosphate) 23 . The demineralisation solution was renewed daily.…”
Section: Methodsmentioning
confidence: 99%
“…Ca (from CaCl 2 ) and 0.002 mol/L P (from potassium phosphate). 23 The demineralisation solution was renewed daily. The prepared samples were kept in the demineralisation solution for 8 h/d until 13-20 values had been obtained using DIAGNOdent, then stored in a dark environment in artificial saliva (prepared by the Atatürk University Faculty of Pharmacy) until the experimental materials were applied.…”
Section: What's Newmentioning
confidence: 99%
“…[35] They work by subjecting the sample to intense pressure and high-velocity fluid flow, which helps break down and disperse the NPs uniformly within the liquid, as shown in Figure 4. [36] The key components of a high-pressure homogenizer include a high-pressure pump, a homogenizing valve or nozzle, and a chamber where the sample is processed. For example, Yujin Hwang reported the dispersion of carbon black in water and Ag NPs in silicon oil using oleic acid and SDS, respectively.…”
Section: Dispersing Of Uncoated Solid Npsmentioning
confidence: 99%
“…Due to the charge of NMs and the charge in the surrounding medium, different layers form around the NPs, as shown in Figure 6 Ref. [36] (Copyright 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim). [43] (Copyright 2015 Public Library of Science (PLOS).…”
Section: Electrostatic Stabilizationmentioning
confidence: 99%